Mengukur E-Participation Masyarakat di Era Transformasi Digital dengan Metode Multi Factor Evaluation Process (MFEP) - Retnowati, Retnowati; Wahyudi, Eko Nur; Anis, Yunus (JUSIFO : Jurnal Sistem Informasi, 2022)
The digital transformation era provides an opportunity for the public to exercise their right to information, where public agency is required to provide documents and information through Pejabat Pengelola Informasi dan Dokumen (PPID). This openness promises an important role for public participation through electronic access to information (E-Information), access to electronic consultations (E-Consultation), and participation in electronic decision-making (E-Decision Making). These three indicators are referred to as E-Participation. However, their implementation has encountered obstacles, leading to the need for research on E-Participation in the current community environment. This study employs a Soft System Methodology approach, specifically the Multi-Factor Evaluation Process (MFEP) method. The objective is to identify the indicators and criteria used in E-Participation, and to determine the level of E-Participation usage in Central Java based on the indicators used. The criteria used in this study pertain to the willingness of both the government and society, as well as the availability of infrastructure and information. The ranking results of the level of E-Participation indicate that public E-Participation is at an average level, where E-Information is the highest strengthening indicator, followed by E-Consultation, and E-Decision Making is the lowest.